Hematometra Ec Stenosis Of The Cervix Of The Uterus: A Case Report - Yenny Mayang Sari; Bobby Indra Utama (Universitas Andalas, 2023)
Background : Cervical stenosis has been defined as a narrowing of the endocervical canal preventing passage of a 2.5-mm Hegar or Pratt dilator. Stenosis of the external cervical os has been described as an external os diameter of less than 4.5mm. Symptoms of cervical stenosis are dependent on the degree of endocervical canal obstruction and the patient's menopausal status. Those patients with severe or complete obstruction of the endocervical canal can experience hematometra with scant or sporadic menstrual flow, amenorrhea, dysmenorrhea, chronic pelvic pain, and infertility.Case Report : A 16-year-old woman was consulted from Pediatric with cervix stenosis with haematometra wich had been noticed since a month ago. Menarche at the age 13 years, regular and slightly pain menstruation every month. The result of MRI examination represented bilateral hematometra and hematocolpos ec suspected cervical stenosis. The management of this case was cervical dilatation and cervical tube installation. Conclusion : Cervical stenosis is a caused of menstrual complaint which is characterized by slightly pain while menstruation, hematometra and hematocolpos.